Interpretasi Caddy Pada Serial Animasi Shaun The Sheep Episode Whoâ€™s The Caddy - -, Handriyotopo; Dewi, Sari Kesuma (Seni Media Rekam ISI Surakarta, 2014)
Â This study describes the interpretation of â€œCaddyâ€ in the animated film series Shaun the Sheep episodes of â€œWhoâ€™s the Caddy?â€ The method used in this research is descriptive qualitative using a semiotic approach of Charles S. Peirce. The primary data of the film is presented in such a visualization of each scene. Data were analyzed in a descriptive narrative form based on mark classification in the process of signification that takes place in the triadic relationship namely representament, interpretant, and object. This study uses the approach to the concept of the mark that divides a sign into three categories: icons, indices, and symbols by using the concept of triangle meaning. From the results of the meaning of these signs can be drawn a conclusion that this study is interconnected. Based on the data analysis, it can be seen that Caddy in the series ofÂ Shaun The SheepÂ episode â€œWhoâ€™s the Caddy?â€ is a symbol that is full of messages. The message reflected through scene after scene that is presented by Caddy is an interpretant that refers to the object. In this case, it represents the three main actors in this episode, they are three golfers (Farmer, Shaun and Bitzer), in which each player is Caddy in a different context. Farmer has become a symbol of the Caddy, Shaun as an index and Bitzer as an icon of Caddy. Caddy represents interpretan, figures (Farmer, Shaun, and Bitzer) represent an object while representamen is a game of golf that has a relationship with the characters. Keywords:Â interpretation, semiotics, and the animated series